2007
DOI: 10.1007/s10350-007-0256-z
|View full text |Cite
|
Sign up to set email alerts
|

Squamous-Cell Carcinoma of the Rectum: A Rare but Curable Tumor

Abstract: PURPOSE: This study was designed to evaluate one institution_s experience with treatment outcomes for rectal squamous-cell carcinoma. METHODS: Using our prospective Colorectal Database, we identified patients diagnosed with rectal squamous-cell carcinoma at our institution between 1983 and 2005. Pathology was rereviewed, tumor immunophenotype was compared to control cases of anal squamous-cell carcinoma and rectal adenocarcinoma, treatment modalities and outcomes were analyzed. RESULTS: Twelve patients were id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
92
1
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(100 citation statements)
references
References 24 publications
2
92
1
5
Order By: Relevance
“…Generally, the treatment is based on that for adenocarcinomas, which is predominantly surgery combined with chemotherapy and radiotherapy. With the advances in chemotherapy and radiotherapy, the accuracy of determining stage and evaluating response, a multitude of recent studies utilizing various treatment regimens have been reported, which included 5-fluorouracil (5FU)/mitomycin C, 5FU, 5FU/cisplatin, capecitabine/cisplatin, capecitabine, raltitrexed/oxaliplatin and S-1 (10,11,.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, the treatment is based on that for adenocarcinomas, which is predominantly surgery combined with chemotherapy and radiotherapy. With the advances in chemotherapy and radiotherapy, the accuracy of determining stage and evaluating response, a multitude of recent studies utilizing various treatment regimens have been reported, which included 5-fluorouracil (5FU)/mitomycin C, 5FU, 5FU/cisplatin, capecitabine/cisplatin, capecitabine, raltitrexed/oxaliplatin and S-1 (10,11,.…”
Section: Discussionmentioning
confidence: 99%
“…The chemoradiation was followed by surgical excision. When radiation therapy was added preoperatively, Nahas showed there was an increase in sphincter preserving procedures from 67% to 71% (15) . Guerra et al recommended that primary treatment should be CRT, with surgery reserved as a salvage option.…”
Section: Discussionmentioning
confidence: 99%
“…Эта молекула будет экспрессироваться аденокарциномами и плоскокле-точным раком прямой кишки, но не анального канала [23]. Также это позволит исключить метастазы рака анального канала в параректальную клетчатку с инва-зией стенки прямой кишки.…”
Section: Discussionunclassified